SIFAT VENIR DAN KAYU LAPIS ENAM JENIS KAYU UNTUK HUTAN TANAMAN INDUSTRI - Rodjak Memed; M I Iskandar; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The characteristics studied are peeling properties, physical properties of the veneer, gluing properties and some physical and mechanical properties of the plywood (both triplex and multiplex).All logs from 6 wood species could be peeled satisfactorily in cold condition. Veneer of 1.5 mm thickness could be produced at cutting angle between 90° 30’- 92°.Average shrinkage of the veneer is 6.52% and average veneer swelling from oven dry to air dry condition is 4.11%. Water resistant bonding strength for all wood species studied meet Indonesian, Japanese and German standard. Average thichness reduction due to pressing in the plywood manufacturing process is 0.31mm. The mechanical properties of plywood vary among the wood species.